Kejadian Drug-Related Problems Pada Pasien Rawat Inap dengan Diabetes Melitus Berdasarkan Kriteria PCNE : Literatur Review - Febriani, Rizkina Elistya; Karuniawati, Hidayah; Rahman, Anees Ur (Journal of Pharmaceutical and Sciences, 2025)
Non-communicable chronic diseases such as diabetes mellitus (DM) are a significant health burden worldwide. In the treatment of DM patients, long-term drug use is inevitable and increases the risk of Drug-Related Problems (DRPs). The presence of DRPs can affect the effectiveness of therapy and the risk of side effects in hospitalized DM patients. This review aims to evaluate various studies conducted on DRPs in hospitalized DM patients based on the Pharmaceutical Care Network Europe (PCNE) classification. A systematic search of relevant articles in the last 10 years through the SpringerLink, ScienceDirect, Scopus, and PubMed databases. Irrelevant studies, review articles, and no data on DRP classification using PCNE or outpatients will be excluded. The review found four articles discussing DRP classification using PCNE in hospitalized DM patients. The number of DRPs varied, ranging from 253 to 873 cases. The proportion of patients experiencing at least one DRP was also relatively high, ranging from 48.1% to 84.5%. The most common problem was treatment ineffectiveness (P1.2), which accounted for more than half of the DRPs in the three studies reviewed, namely 62.0%, 79.6%, and 52.7%. The most common cause of DRPs came from the patient-related domain (C7.1) at 71.85%. Other domains that caused DRPs were the Drug use domain (C6.1) at 62.0%, other domains (C9) at 40.9%, the drug selection domain (C1.6) at 26%, and the dose selection domain (C3.5) at 25.9%. The occurrence of DRPs is a significant problem in the management of diabetes mellitus, especially in the hospital environment. The ineffectiveness of therapy is the main problem of DRPs. The high number of DRPs from other domains indicates that many causes of DRPs are not classified explicitly in the PCNE category.